Stability and error estimates of BV solutions to the Abel inverse problem. (1st August 2018) - Zhang, Linan; Schaeffer, Hayden
Abstract: Reconstructing images from ill-posed inverse problems often utilizes total variation regularization in order to recover discontinuities in the data while also removing noise and other artifacts. Total variation regularization has been successful in recovering images for (noisy) Abel transformed data, where object boundaries and data support will lead to sharp edges in the reconstructed image. In this work, we analyze the behavior of solutions to the Abel inverse problem, deriving a priori estimates on the recovery. In particular, we provide L 2 -stability bounds on solutions to the Abel inverse problem. These bounds yield error estimates on images reconstructed from a proposed total variation regularized minimization problem.